2008
DOI: 10.2308/iace.2008.23.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Using Action Research to Improve Learning and the Classroom Learning Environment

Abstract: To a large extent, research in business and the social sciences is based on theoretical constructs about existing organizations, phenomena, or behavior, followed by tests of hypotheses derived from these constructs. The goal usually is to describe or explain the organizations, phenomena, or behavior being studied and/or to generalize the findings to future organizations, phenomena, or behavior. Conversely, the goal of action research is to effect a desirable change within a specific social setting—one in which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
65
0
17

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(83 citation statements)
references
References 6 publications
1
65
0
17
Order By: Relevance
“…A study by Cunningham (2008) provided mixed results as to students' perceptions of RRD but found that a majority of the students studied indicated that the devices added interest to the class. Findings by Robinson (2006), Robinson and Ritzko (2006), and Bode et al (2009) also indicated that most students reported increased class participation when clickers are used in the course.…”
Section: Literature Reviewmentioning
confidence: 99%
“…A study by Cunningham (2008) provided mixed results as to students' perceptions of RRD but found that a majority of the students studied indicated that the devices added interest to the class. Findings by Robinson (2006), Robinson and Ritzko (2006), and Bode et al (2009) also indicated that most students reported increased class participation when clickers are used in the course.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In this type of lecture, the focus is on the lecturer, and the students are not compelled to be actively involved in the learning process (Cooper and Robinson, 2000;Killen, 2010). It was found that a lecturer-centred approach transfers information less efficiently, and is less effective in the long term than more interactive and participatory methods, as students generally only remember 10-20 per cent of what they hear (Biggs, 2000;Cooper and Robinson, 2000;Cunningham, 2008;Killen, 2010). The student-centred approach (in many ways, the antithesis of the lecturer-centred approach) has proved to be a more effective way of transferring skills and literacy to new generation students (Cooper and Robinson, 2000;Killen, 2010) in that it gets them actively involved in the learning process.…”
Section: Literature Reviewmentioning
confidence: 99%
“…There is growing consensus among researchers about the positive effects of co-operative learning on student achievement (Aziz and Hossain, 2010;Ballantine and Larres, 2009;Ballantine and Larres, 2007;Johnson and Johnson, 1987;Slavin, 1996). In that students learn from one another by hearing, thinking about and reasoning through opposing points of view, also contributes to development of higher-order thinking (Cunningham, 2008). Studies conducted in accounting education have indicated that cooperative learning approaches are essential for the development of key professional skills in accounting students, as teamwork is considered to be very important by prospective employers (Ballantine and Larres, 2007;Barac, 2009;Bui and Porter, 2010;Gabbin and Wood, 2008;Hall et al, 2007).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Some see it as a more clear-cut concept, yet they define it with a similar complexity. For example, according to Cunningham (2008), action research "is a value-driven, cyclical, and transformative process that uses intervention in a setting, based on observation and theoretical constructs, to alleviate an observed problem or to increase the effectiveness of a practice in the setting" (p. 1).…”
Section: Action Researchmentioning
confidence: 99%